Anesthetic implications of infants with mandibular hypoplasia treated with mandibular distraction osteogenesis. Issue 4 (9th October 2012) - Frawley, Geoff; Espenell, Ainsley; Howe, Peter; Shand, Jocelyn; Heggie, Andrew
Summary: Objectives: To document the incidence of difficult intubation following mandibular distraction osteogenesis (MDO) in children with severe mandibular hypoplasia. Background: Syndromes associated with significant mandibular hypoplasia, especially Pierre Robin sequence, provide a challenge in airway management both in and out of the operating room. Mandibular advancement using mandibular distraction osteogenesis devices has been used in infants in an attempt to reduce the incidence of acute life‐threatening airway obstruction. Whether MDO also reduces the incidence of difficult intubation has not been adequately described. Methods: A retrospective chart review of 51 infants with upper airway obstruction secondary to mandibular hypoplasia who required MDO between January 2002 and 2012. The primary outcome was the incidence of difficult or failed intubation. Secondary outcomes were the relationship between syndrome type and the incidence of difficult intubation. Results: Fifty‐one PRS infants were identified. Twenty‐eight patients had isolated PRS, six had syndromic PRS, seven had Treacher Collins syndrome, and 10 had another coexisting syndrome. Prior to mandibular distraction osteogenesis (MDO), the incidence of difficult intubation was 71%, with the highest incidence in patients with Treacher Collins syndrome (100%), sPRS syndrome (100%), and PRS (65%). Following MDO, the incidence of difficult intubation was 8.3%. The difference was statistically significant for all patients (Kruskal–Wallis rank test P = 0.0001) those with isolated PRS ( P = 0.0001), syndromic PRS ( P = 0.0023), and other syndromes ( P = 0.0002), but not for Treacher Collins syndrome ( P = 0.21). Three patients had pre existing tracheostomies. Conclusions: In a select group of infants with severe upper airway obstruction who have failed nonsurgical airway interventions, mandibular distraction osteogenesis reduces the incidence of difficult mask ventilation and difficult intubation. We were not able to compare the improvement in airway management to a comparable group of PRS infants who did not undergo surgical intervention. The improvement in laryngeal view was most marked for infants with isolated PRS but no significant benefit was demonstrated in infants with TCS.